2017
DOI: 10.1007/s00449-017-1764-4
|View full text |Cite
|
Sign up to set email alerts
|

Production and partial characterization of biosurfactant produced by Streptomyces sp. R1

Abstract: The present study focused on developing a wild-type actinomycete isolate as a model for a non-pathogenic filamentous producer of biosurfactants. A total of 33 actinomycetes isolates were screened and their extracellular biosurfactants production was evaluated using olive oil as the main substrate. Out of 33 isolates, 32 showed positive results in the oil spreading technique (OST). All isolates showed good emulsification activity (E) ranging from 84.1 to 95.8%. Based on OST and E values, isolate R1 was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
2
12
0
5
Order By: Relevance
“…Additionally, the emulsification index results for hydrocarbons assessed in this work were similar to those published by [ 57 ]. An emulsification index of 80% was reported for petroleum, according to Zambry et al [ 58 ], similar to those obtained in our work for oils of grades APIa 33.9° and APIm 28.6°, where an emulsification index of 90% was reached. With these results, we highlight the carbon source n-Hexadecane as a good substrate for the production of surface active biomolecules using the Antarctic strain Streptomyces luridus , with a high emulsification capacity for both oils and vegetable oils.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the emulsification index results for hydrocarbons assessed in this work were similar to those published by [ 57 ]. An emulsification index of 80% was reported for petroleum, according to Zambry et al [ 58 ], similar to those obtained in our work for oils of grades APIa 33.9° and APIm 28.6°, where an emulsification index of 90% was reached. With these results, we highlight the carbon source n-Hexadecane as a good substrate for the production of surface active biomolecules using the Antarctic strain Streptomyces luridus , with a high emulsification capacity for both oils and vegetable oils.…”
Section: Resultssupporting
confidence: 91%
“…These results are similar to those reported in [ 57 ] who observed that the use of glycerol and glucose (hydrophilic molecules) as carbon sources did not stimulate the production of surface-active molecules such as biosurfactants. Furthermore, Zambry demonstrated that glycerol used as the only source of carbon in culture media is not appropriate for the production of surfactant biomolecules by bacterial strains belonging to the genus Streptomyces [ 58 ]. Additionally, the same work demonstrated that a strain of Streptomyces has the ability to produce biosurfactants through stimulation with olive oil.…”
Section: Resultsmentioning
confidence: 99%
“…Out of nine isolates, only two isolates, RG3 and RG8, showed positive results. During the screening process, olive oil was used as the carbon source for biosurfactant production was increased using actinomycetes [25]. One of the parameters for selecting potential producer biosurfactants is the emulsification activity.…”
Section: Isolation and Production Of Biosurfactantsmentioning
confidence: 99%
“…These are mainly produced by Pseudomonas aeruginosa strains and in comparison to chemical surfactants exhibit higher bio-degradability, low-toxicity, increased surface activities, longer shelf life, high selectivity and specificity at extreme pH, temperature and salinity ranges [3]. Additionally, biosurfactants display anti-microbial, anti-tumorous, anti-adhesive, anti-oxidant and anti-corrosive activities [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Over a period of 2016 -2023, this prominent product is projected to witness the highest compound annual growth rate of 7.5%, with a market of 250 kilotons by 2024 worth 2.7 billion USD [6]. However, its commercialization is hindered due to (i) low yields (ii) cost intensive recovery and (iii) high production costs [4]. In order to overcome these bottlenecks, research has been directed towards isolation of new isolates, media optimization and the use of renewable substrates, especially from agro-industrial wastes.…”
Section: Introductionmentioning
confidence: 99%